PEMANFAATAN RUANG TERBUKA HIJAU DALAM MENINGKATKAN KUALITAS LINGKUNGAN KABUPATEN BENGKAYANG - Aristo, Aristo (LPPM Institut Teknologi dan Bisnis Kristen Bukit Pengarapan, 2023)
The environment is where various living things interact, including humans. Every year, the environment experiences a significant decline that threatens survival. Attitudes and actions to care for the environment are essential to prevent and restore its adverse effects. Green Open Space (RTH) is emerging as an alternative in rapidly urbanizing areas, such as Bengkayang Regency. RTH has a key role in maintaining ecosystems and providing recreational space. Collaboration with the Environmental Agency is the basis of empowerment in Bengkayang Regency. The activities carried out are garbage cleaning, routine maintenance, planting vegetation and trees, and urban greening. The benefits of RTH involve ecological, social and economic aspects. The use of RTH relieves stress, improves well-being, and creates a place for social interaction. Although population and industrial growth have negative impacts, the utilization of RTH can address ecological and social concerns with wise planning. Through proper design, development, and management, Bengkayang Regency can maintain environmental quality and improve welfare. The creation of appeal signs is also effective in educating the public about the importance of keeping the environment clean.